Private Universities in Nigeria: Contributions, Problems and Way Forward - Niyi Jacob Ogunode; Conrad Ugochukwu Ukozor; Olowonefa Jethro Abiodun (International Journal of Educational and Life Sciences, 2024)
This paper discussed the contributions and problems militating against the development of Private universities in Nigeria. Adopting content analysis and elimination methods that were used for data selection. The paper used secondary data that were collected from print and online publications. The paper identified increment in access to university education, manpower development and production, development of research, community services, creation of employment opportunities and improvement in international ranking as contributions of private universities to the Nigerian economy. Problems of funding, shortage of modern infrastructure facilities, lack of access to funds and government support, low student enrolment, inadequate academic staff and insecurity problems are the problems militating against the development of Private universities in Nigeria. Based on this, the paper hereby recommended that the federal government should establish special intervention financial institutions for private universities across the country where they can secure long and short-term facilities with low interest. Private university managers should utilize their Alumni association to raise more funds and technical support. Private universities should explore the option of public-private partnerships to develop their infrastructure facilities.